2013
DOI: 10.1523/jneurosci.5274-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β1–42Slows Clearance of Synaptically Released Glutamate by Mislocalizing Astrocytic GLT-1

Abstract: GLT-1, the major glutamate transporter in the adult brain, is abundantly expressed in astrocytic processes enveloping synapses. By limiting glutamate escape into the surrounding neuropil, GLT-1 preserves the spatial specificity of synaptic signaling. Here we show that the amyloid-␤ peptide A␤ 1-42 markedly prolongs the extracellular lifetime of synaptically released glutamate by reducing GLT-1 surface expression in mouse astrocytes and that this effect is prevented by the vitamin E derivative Trolox. These fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
123
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(130 citation statements)
references
References 28 publications
7
123
0
Order By: Relevance
“…Recent studies have demonstrated that synthetic oligomeric Ab 1-42 decreased GLT-1 expression or promoted mislocalization of GLT-1 from the cell surface of primary astrocytes, leading to glutamate dyshomeostasis in synapses (Abdul et al, 2009;Scimemi et al, 2013). Our in vivo evidence (Fig.…”
Section: Resultssupporting
confidence: 58%
“…Recent studies have demonstrated that synthetic oligomeric Ab 1-42 decreased GLT-1 expression or promoted mislocalization of GLT-1 from the cell surface of primary astrocytes, leading to glutamate dyshomeostasis in synapses (Abdul et al, 2009;Scimemi et al, 2013). Our in vivo evidence (Fig.…”
Section: Resultssupporting
confidence: 58%
“…They provide valuable tools that can be used to estimate the lifetime of glutamate in the extracellular space at different stages of development 13 in a variety of animal species 14 and brain regions under physiological and pathological conditions 21 .…”
Section: Discussionmentioning
confidence: 99%
“…In cultured astrocytes, surface expression of GLT-1, but not GLAST, is reduced following incubation with Aβ1-42 (500 nM) [133]. In the hippocampus of mice, however, the expression of both GLT-1 and GLAST is reduced following injection of Aβ1-40 (400 pmol/site) [135].…”
Section: Aβ and Excitotoxicitymentioning
confidence: 99%
“…Another way in which Aβ can increase extracellular concentrations of glutamate is by inhibition of astrocytic uptake, resulting in an increased duration of glutamate in the synaptic cleft [131][132][133][134][135]. In cultured astrocytes, surface expression of GLT-1, but not GLAST, is reduced following incubation with Aβ1-42 (500 nM) [133].…”
Section: Aβ and Excitotoxicitymentioning
confidence: 99%
See 1 more Smart Citation